CITRA PEREMPUAN ISLAM DALAM NOVEL BUMI BIDADARI KARYA TAUFIQURRAHMAN AL-AZIZY - Rachmiati, Ami Siti; Martono, Martono; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated desire of researcher to find a female image of Islam in the novel Bumi Bidadari created by Taufiqurrahman Al-azizy. Special problems in this research are how the physical image of Islam women? How the psychological image of Islam women? In this research uses literature theory about the novel elements and the image theory of Islam women. The research uses descriptive method with qualitative terms. It uses structural dynamic approach. Data resources use some citations novel entitled Bumi Bidadari created by Taufiqurrahman Al-azizy. Technical examination of the validity data that is perseverance observation, triangulation, and adequacy of reference. The analysis technique used to analyze and interpret the image of Islam women which divided into the physical image of Islam women and the psychological image of Islam women, as well as discuss and summarize the result of research in order to obtain a description of the image of Islam women. The result research involves: 1) The physical image of Islam women, such as: a) facial beauty, b) body posture, and c) appearance style. 2) The psychological image Â Islam women, such as: a) bashfulness, b) qanaah, c) courageous, d) impartiality, e) maintaining morals. Advice for readers can benefit from novel Bumi Bidadaricreated by Taufiqurrahman Al-azizy.Key words: Islam, women, novel.